Strategi Pemasaran Pembiayaan Ijarah Muntahiyah Bit-Tamlik (IMBT) terhadap Pemberdayaan Usaha Mikro Kecil Menengah - M. Manshur Idris; Mustofa Mustofa (Istidlal: Jurnal Ekonomi dan Hukum Islam, 2019)
Islamic finance institutions are often used as an alternative for the community that is not facilitated by banks, both conventional and Islamic. People tend to invest their capital and run financing in shari'ah financial institutions because administrative procedures are easy when compared to investing capital and financing in State or private banks and also because they are more reliable. The purpose of this study was to determine the marketing strategy of financing Ijarah Muntahiyah Bit-Tamlik (IMBT) and the effect of IMBT financing on the empowerment of Micro, Small and Medium Enterprises (UMKM). The location of this study was at KSPS BMT UGT Sidogiri Capem Silo Jember. This research is qualitative descriptive method. Data collection was done through interviews, observation, and documentation. The analysis was carried out by data reduction, data presentation, data collection, and triangulation. The results showed that the marketing strategy of IMBT financing applied by BMT Sidogiri Capem Silo Jember included four variables in the marketing mix, namely product strategy, promotion strategy, pricing strategy, and place strategy. Whereas the effect of IMBT financing on the empowerment of UMKM was that develops productive businesses to increase the income of small entrepreneurs and members, one of which was in the trade and agriculture sectors to facilitate the public in accessing their goods.